2022
DOI: 10.3390/jpm12121999
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressive Role of the PRELP Gene in Ovarian Clear Cell Carcinoma

Abstract: Ovarian clear cell carcinoma (OCCC) has a poor prognosis, and its therapeutic strategy has not been established. PRELP is a leucine-rich repeat protein in the extracellular matrix of connective tissues. Although PRELP anchors the basement membrane to the connective tissue and is absent in most epithelial cancers, much remains unknown regarding its function as a regulator of ligand-mediated signaling pathways. Here, we obtained sets of differentially expressed genes by PRELP expression using OCCC cell lines. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Proteins that have low or no expression in saliva or salivary glands were also excluded from the validation list. The final shortlisted hits, namely, peroxiredoxin‐4 (PRX‐IV), legumain, SIL1 nucleotide exchange factor (SIL1), and cellular repressor of E1A‐stimulated genes (CREG1), were chosen based on novelty, 27–41 and the absence of association with other oral diseases 42–47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins that have low or no expression in saliva or salivary glands were also excluded from the validation list. The final shortlisted hits, namely, peroxiredoxin‐4 (PRX‐IV), legumain, SIL1 nucleotide exchange factor (SIL1), and cellular repressor of E1A‐stimulated genes (CREG1), were chosen based on novelty, 27–41 and the absence of association with other oral diseases 42–47 …”
Section: Resultsmentioning
confidence: 99%
“…Proteins that have low or no expression in saliva or salivary glands were also excluded from the validation list. The final shortlisted hits, namely, peroxiredoxin-4 (PRX-IV), legumain, SIL1 nucleotide exchange factor (SIL1), and cellular repressor of E1A-stimulated genes (CREG1), were chosen based on novelty, [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and the absence of association with other oral diseases. [42][43][44][45][46][47] 2.2 | Salivary PRX-IV and legumain are significantly upregulated in HFMD case samples from Singapore Dot blot validation assay was performed using saliva samples from HFMD-diagnosed patients and healthy volunteers in Singapore to assess the sensitivity and specificity of the respective biomarker(s).…”
Section: Nineteen Salivary Proteins Were Significantly Upregulated In...mentioning
confidence: 99%
“…In addition, we demonstrated that Prelp was expressed in mouse retina and loss of Prelp contributed to retinoblastoma cell progression by reducing cell-cell adhesion and facilitated EMT (Hopkins et al, 2022). We further investigated the roles in other tumors and identified that PRELP showed a tumor suppressive role by regulated PI3K-AKT signalling pathway in highgrade ovarian cancer (Dozen et al, 2022).…”
Section: Methodsmentioning
confidence: 92%
“…There exists increasing evidence about the clinical relevance of PRELP as a tumor suppressor in solid tumors and its use as a prognostic marker [ 30 , 38 , 84 ]. In this study, the PRELP expression status was significantly associated with the patients’ prognosis.…”
Section: Discussionmentioning
confidence: 99%